2005
DOI: 10.1002/anie.200501818
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Fully Synthetic Carbohydrate‐Based Anticancer Vaccine: Synthesis and Immunological Evaluation of a Lipidated Glycopeptide Containing the Tumor‐Associated Tn Antigen

Abstract: A spoonful of sugar …︁ A carbohydrate‐based fully synthetic vaccine 1, composed of a tumor‐associated Tn antigen, a peptide T epitope, and a lipopeptide (see structure), shows potential as a candidate against cancer. Incorporation of the glycolipopeptide into liposomes gave a formulation that was able to elicit a T cell dependent antibody response in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(92 citation statements)
references
References 40 publications
0
92
0
Order By: Relevance
“…In addition, bacterial lipopeptides have been studied as adjuvants for anti-tumor [53] and immunocontraceptive [50,54] vaccines.…”
Section: Fig (1)mentioning
confidence: 99%
“…In addition, bacterial lipopeptides have been studied as adjuvants for anti-tumor [53] and immunocontraceptive [50,54] vaccines.…”
Section: Fig (1)mentioning
confidence: 99%
“…14.10). A first construction (12) was composed of Pam 3 Cys, the Tn antigen, and the T-cell epitope peptide "YAF" derived from an outer-membrane protein of Neisseria meningitidis [37].…”
Section: Lipid Carriersmentioning
confidence: 99%
“…Finally, a fully synthetic approach makes it possible to optimize the various components of the candidate vaccine by structure-activity relationship studies. In this respect, proper design of the three-component vaccine is essential, because previously we showed that a compound composed of the inferior adjuvant Pam 3 Cys which lacks the important tetra-lysine moiety and a human Th epitope elicits low titers of IgG antibodies 7,14 . Furthermore, it has been found that covalent attachment of the three components is important for optimal antigenic responses.…”
Section: Online)mentioning
confidence: 99%
“…In addition, foreign carrier proteins such as keyhole limpet hemocyanin (KLH) and bovine serum albumin (BSA) and the linker that attach the saccharides to the carrier protein can elicit strong B-cell responses, which may lead to the suppression of antibody responses against the carbohydrate epitope 5,6 . It is clear that the successful development of carbohydrate-based cancer vaccines requires novel strategies for the more efficient presentation of tumor-associated carbohydrate epitopes to the immune system, resulting in a more efficient class switch to IgG antibodies [7][8][9][10][11][12][13][14][15][16][17] .…”
mentioning
confidence: 99%